When we simplify (3 + √5)(3 + √2), the result obtained is:
9 + 3√2 + 3√5 + √10
<h3>Surd operation </h3>
a√b × c√d = (a × c)√(b × d)
<h3>How to simplify (3 + √5)(3 + √2)</h3>
(3 + √5)(3 + √2)
Expand by clearing the bracket
3(3 + √2) + √5(3 + √2)
9 + 3√2 + 3√5 + √10
Thus,
(3 + √5)(3 + √2) = 9 + 3√2 + 3√5 + √10
Learn more about surd:
brainly.com/question/24700530
#SPJ1
Answer:
NO
Step-by-step explanation:
bc
u
ha ve
aut
tis
umm
and
special
kid
home
work
Answer: 17 cm
Step-by-step explanation:
84 - 25(2) = 2x
84 - 50 = 2x
34 = 2x
x = 17
17 cm
Answer:
C
Step-by-step explanation:
Ohio's resources support manufacturing equipment.
Answer:
2/1 or 2
Step-by-step explanation:
You go up 6 and over 3 simplify 6/3 to 2/1=2